(3eYGde GdJfRjds - (3GdMSjf Hf eSYhO Hf eMeO, GdaqQGA, Ch GHf GdnanqQGA, CHh eMeO, hjdbH HeMjj GdSqfI, GdHZhj,J (B510 (3g` s ((3GHh WGgQ CMeO Hf eMeO Hf eMeO Hf YeQ Hf CMeO GdhGYX jYQa hGdOg HGdUQGa s)
(3ChdgG (B:s
(3HJaSjQ ShQI eQje Hbhdg bhdg YR hLd cgjYU bQC CHh YeQ HcSQ GdgGA haJM GdjGA VOg GHf YGeQ hMeRI HcSQgeG s
(3BNQgG (B:s
(3ef JaSjQ ShQI GdfGS bhdg Yf CHj gQjQI Gfg SeY GdfHi Udi Gddg Ydjg hSde Hbhd eG GPf Gddg dfHi MSf GdUhJ HGdbQBf jLgQ Hg Je cJGH eYGde GdJfRjd s
(3GdfSNI HgG MhGTs
(3HBNQgG Jedc SfI (B728s
(3HChQGbgG BKGQ JbWjYs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJaSjQ hYdhe GdbQBfs